1998
DOI: 10.1037/0022-0167.45.4.414
|View full text |Cite
|
Sign up to set email alerts
|

Ratings of helper roles by multicultural psychologists and Asian American students: Initial support for the three-dimensional model of multicultural counseling.

Abstract: We thank Joyce Fujimaki, Heidi Kwok, and Aimee Truong for their assistance in collecting and entering data and Rebecca Zwick for her assistance with data analysis. Financial support for this project was provided by the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…The results showed that Asian Americans favor a logical, rational, directive, and culturally attentive counseling style over a reflective, affective, nondirective, and less culturally attentive one (Atkinson, Maruyama, & Matsui, 1978;Gim, Atkinson, & Kim, 1991), especially if the counselor is described as an Asian American (Atkinson & Matsushita, 1991). The results also suggested that Asian Americans prefer counselors who use the consultant helping role when the presenting problem has an external etiology (e.g., racism) and the role of the facilitator of indigenous support systems when the problem has an internal etiology (e.g., depression; Atkinson, Kim, & Caldwell, 1998). Although these studies provide useful information, an important limitation is the possible lack of external validity of the results as related to the actual client population because the participants were not actual clients seeking services at a counseling agency.…”
mentioning
confidence: 89%
“…The results showed that Asian Americans favor a logical, rational, directive, and culturally attentive counseling style over a reflective, affective, nondirective, and less culturally attentive one (Atkinson, Maruyama, & Matsui, 1978;Gim, Atkinson, & Kim, 1991), especially if the counselor is described as an Asian American (Atkinson & Matsushita, 1991). The results also suggested that Asian Americans prefer counselors who use the consultant helping role when the presenting problem has an external etiology (e.g., racism) and the role of the facilitator of indigenous support systems when the problem has an internal etiology (e.g., depression; Atkinson, Kim, & Caldwell, 1998). Although these studies provide useful information, an important limitation is the possible lack of external validity of the results as related to the actual client population because the participants were not actual clients seeking services at a counseling agency.…”
mentioning
confidence: 89%
“…For example, a counselor working with a recent immigrant to the United States (low acculturation) who is currently in the midst of a housing discrimination conflict (external etiology of the problem and the need for remediation as the goal of counseling) would assume the role of an advocate for the client. In a survey of psychologists and Asian American college students, Atkinson, Kim, and Caldwell (1998) found support for validity of the three-dimensional model.…”
Section: Using Games To Instill Competency In the Skills Dimensionmentioning
confidence: 99%
“…Ever since the creation of the counseling profession, there has been ongoing debate over the professional counselor's role. Initially, this debate centered on conventional roles counselors perform in education settings: personal counseling, career counseling, consultation, assessment and research, program development, and psychotherapy (Atkinson, Kim, & Caldwell, ). There are those who argue that counselors should play a more conventional role in providing individual counseling (Canfield, ).…”
Section: A Need For a New Discourse In Counselingmentioning
confidence: 99%